Hepatic Arterial Vasodilation Is Independent of Portal Hypertension in Early Stages of Cirrhosis - Moeller, Miriam (PLoS One, 2015)
INTRODUCTION: The compensatory increase in hepatic arterial flow with a decrease in portal venous flow is known as the hepatic arterial buffer response. In cirrhosis with elevated portal pressure, the vascular resistance of the hepatic artery is decreased. Whether this lower resistance of the hepatic artery is a consequence of portal hypertension or not remains unknown. STUDY AIM: The aim of the study was to investigate the hepatic arterial resistance and response to vasoconstriction in cirrhosis without portal hypertension (normal portal resistance). METHODS: Cirrhosis was induced by CCl(4)-inhalation for 8 weeks (8W, normal portal resistance) and for 12–14 weeks (12W, elevated portal resistance). Bivascular liver perfusion was performed at 8W or 12W and dose response curves of methoxamine were obtained in the presence or absence of LNMMA (nitric oxide synthase blocker). Vascular resistances of the hepatic artery (HAR), portal vein (PVR) and sinusoids (SVR) were measured. Western Blot (WB) and Immunohistochemistry (IHC) were done to measure eNOS and HIF 1a expression. RESULTS: HAR in both groups of cirrhotic animals (8W and 12W) were lower compared to controls. Dose response curves to methoxamine revealed lower HAR in both cirrhotic models (8W and 12W) regardless the magnitude of portal resistance. LNMMA corrected the dose response curves in cirrhosis (8W and 12W) to control. WB and IHC show increased protein expression of eNOS and HIF1a in 8W and 12W. CONCLUSION: Hepatic arterial resistance is decreased in cirrhosis independent of portal resistance. Vasodilation of the hepatic artery in cirrhosis seems to be influenced by hypoxia rather than increase in portal resistance. Nitric oxide is the main vasodilator.